Family planning practice among Christian health service providers in Ghana: a case study - James Duah; Peter Yeboah (Health for All Nations, 2017)
Introduction: The interphase of faith and practicing health professionally often presents a challenge. To navigate between the two requires tact, experience, and professionalism. Such is the case of the Christian Health Association of Ghana (CHAG). Objective: This case report presents an overview of how the Christian Health Association has provided family planning services for marginalized communities in Ghana by Church denominations some of whose doctrines forbid them from practicing certain forms of family planning. Background: CHAG is a network of 300 health facilities and health training institutions owned by 25 different Christian church denominations. CHAG provides health care to the vulnerable, deprived, and marginalized population groups in all 10 regions of Ghana. As an implementing partner of the Ministry of Health, CHAG is mandated to implement key policies to achieve national health outcomes, including family planning. Some members do not accept artificial family planning on the account of religious faith. This often presents a challenge in addressing the need to provide family planning services as required. This challenge is further complicated by the fact that the CHAG secretariat charged with protecting the interests of member institutions as well as those of the ministry. Strategy: CHAG tailors the provision of family planning interventions to denominational, socio-cultural, and religious acceptability, and client needs. Results: Over a period of three years, the proportion of family planning acceptors who are adolescents (10-19 years) increased from 13.7 percent to 17.0 percent, total family planning acceptors increased from 67,312 to 73,648 and total couple years of protection increased from 71,296 to 92,852. Male sterilization also increased, contrary to cultural beliefs. Importantly, CHAG as an implementing partner is able to satisfy its obligation of providing service to achieve national health goals. Conclusion: Protecting the interests of Christian health institutions and those of government may conflict at some point. Being tactful and allowing work within the confines of faith and obligations helps in achieving desired results.